Narrative sources concerning the Polish community in Bosnia and Herzegovina in the Austro-Hungarian period - Lis, Tomasz Jacek (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In my paper I make an attempt to present the current state of knowledge on the source base concerning the Polish community in Bosnia and Herzegovina in the Austro-Hungarian period. I analyze exclusively narrative sources, which I classified according to the Polish groups which appeared there (peasants, intelligentsia and soldiers). I also evaluate the usefulness of those narrative sources in my research. I briefly characterized each source naming its author, the context as well as the approximate date of the appearance of a given source, which will certainly contribute to the further research.